Stronger Is Better: The Impact of Upper Body Strength in Double Poling Performance - Sunde, Arnstein; Johansen, Jan-Michael; Gjøra, Martin; Paulsen, Gøran; Bråten, Morten; Helgerud, Jan; Støren, Øyvind (Frontiers in Physiology, 2019)
The purpose of the present study was to compare time results from a roller-skiing double poling (DP) time trial with different physiological variables, muscular strength variables and DP characteristics in both male and female young competitive skiers with the same relative training background. In order to do this, 28 (16 women and 12 men) well-trained 16-25-year-old cross-country skiers from three Norwegian high schools for skiers, as well as local high performance competitive skiers from the South-East of Norway were recruited to participate in the study. All participants were tested for; maximal oxygen uptake in running, Peak oxygen uptake in DP, lactate threshold in DP, DP economy, time to voluntary exhaustion in DP, force analyses in DP, one repetition maximum and power output in pulldown and leg press and a time trial during DP roller skiing. The results expressed strong correlations between roller skiing time trial performance and maximal strength in pull-down, both independent (r = -0.83, p < 0.00, normal correlation) and dependent (r = -0.50, p < 0.02, partial correlation) of sex. Higher maximal upper body strength was related to higher DP peak forces (PF) (r = 0.78, p < 0.00, normal correlation), lower DP frequency (r = -0.71, p< 0.00) and shorter DP contact time (CT) (r = -0.48, p < 0.02, normal correlation). The practical implications of the present study is to acknowledge maximal upper body strength as a performance determining factor in double poling. This points at the importance of including maximal strength training in the cross-country skiers training programs.